Cyanidin, Malvidin and Pelargonidin Content of “Kolang-kaling” Jams Made with Juices from Asian Melastome (Melastoma malabathricum) Fruit, Java Plum (Syzygium cumini) Fruit Rind or Mangosteen (Garcinia mangostana) Fruit Rind - Yenrina, Rina; Sayuti, Kesuma; Nakano, Kohei; Thammawong, M.; Anggraini, Tuty; Fahmy, Khandra; Syukri, Daimon (Pakistan Journal of Nutrition, 2017)
Background and Objective: A previous study showed that anthocyanins are present in Asian melastome fruit, java plum fruit rind and mangosteen fruit rind, as well as the juices from these fruits, but these juices impart different colors when added to "kolang-kaling" jam. This study was conducted to identify 3 types of anthocyanin, Pelargonidin-3-glucoside chloride, malvidin-3-5-diglucoside chloride and cyanidin-3-0-glucoside chloride, in Asian melastome fruit, java plum fruit rind, mangosteen fruit rind and in "kolang-kaling" jam made with juice from these fruits and rinds. Materials and Methdos: Pelargonidin, malvidin and cyanidin content in the fruits and rinds was analyzed using a Thermo Ultimate 3000 HPLC with a CD-C18, 3 μm Cadenza column at a column temperature of 35°C. Results: The fruits and rinds did not contain pelargonidin-3-glucoside chloride, whereas, malvidin-3-5-diglucoside chloride was found only in java plum fruit rind and cyanidin-3-0-glucoside chloride was present only in Asian melastome fruit. Conclusion: The cyanidin-3-0-glucoside chloride and malvidin-3-5-diglucoside chloride contents increased linearly with addition of increasing amounts of juices from these fruits or rinds during "kolang-kaling" jam production.